Numerical simulation of angled surface crack detection based on laser ultrasound - Han, Shiwei; Lian, Yudong; Xie, Luyang; Hu, Qi; Ding, Jie; Wang, Yulei; Lu, Zhiwei (Frontiers in Physics, 2022)
As an important branch of non-destructive testing, laser ultrasonic testing has attracted increasing attention in the field of material testing because of its instantaneity, non-contact and wide adaptability. Based on the finite element method, the process of laser-excited ultrasonic signal is numerically simulated, and the influence of angled cracks on the ultrasonic signal is analyzed. In this paper, the effects of the time function, pulse width, and spot radius of a Gaussian light source are analyzed through the transient field. The different modes of the ultrasonic signal are used to fit the crack’s angle, depth, and width to complete the characteristic analysis of the surface angled crack. The results show that the displacement peak-valley difference of the direct Rayleigh wave is negatively correlated with the crack angle. The displacement extremes of the transmitted Rayleigh wave boundary are negatively correlated with crack depth and width, while the transmitted Rayleigh wave is positively correlated. This paper presents a method for the quantitative analysis of surface-angled cracks and provides a theoretical basis for further experimental verification.